Subjects of the system of public exposure of convicted in Kazakhstan: new approaches and prospects (Journal of actual problems of jurisprudence, 2019)
In this article, the author reveals features of subjects interacting with the public correctional institutions in the Republicof Kazakhstan, and on the basis of this analysis determines the system and prospects of development of the subjects ofsocial infl uence on the convicts in the modern period.Key words: Public Advisory Council, Public Advisory Commission, Criminal – Executive Code, Councils of Mentors,amateur organizations of convicts.